2012
DOI: 10.1177/0093854812451088
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Responsive Lessons Learned and Policy Implications for Women in Prison

Abstract: The authors review evidence of gender-responsive factors for women in prisons. Some gender-responsive needs function as risk factors in prison settings and contribute to women's maladjustment to prison; guided by these findings, the authors outline ways in which prison management, staff members, and programming can better serve female prisoners by being more gender informed. The authors suggest that prisons provide treatment and programming services aimed at reducing women's criminogenic need factors, use gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
157
1
11

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(175 citation statements)
references
References 74 publications
(163 reference statements)
6
157
1
11
Order By: Relevance
“…Importantly, the study found that the effects of several variables (e.g., age, Illegal Activity Scale, social rule breaking score) were dependent on the time elapsed since release from jail, whereas others (e.g., substance use severity and parental status) had more persistent effects over time. Overall, these findings support the development of re-entry services tailored for female offenders that address both gender-responsive and gender-neutral criminogenic risk factors (Wright, Van Voorhis, Salisbury, & Bauman, 2012). Moreover, the effects of several variables in the immediate re-entry period support the development of transition planning that aims to limit gaps in services for women upon release and their referral to treatment and other services.…”
Section: Criminogenic Predictorsmentioning
confidence: 56%
“…Importantly, the study found that the effects of several variables (e.g., age, Illegal Activity Scale, social rule breaking score) were dependent on the time elapsed since release from jail, whereas others (e.g., substance use severity and parental status) had more persistent effects over time. Overall, these findings support the development of re-entry services tailored for female offenders that address both gender-responsive and gender-neutral criminogenic risk factors (Wright, Van Voorhis, Salisbury, & Bauman, 2012). Moreover, the effects of several variables in the immediate re-entry period support the development of transition planning that aims to limit gaps in services for women upon release and their referral to treatment and other services.…”
Section: Criminogenic Predictorsmentioning
confidence: 56%
“…However, given the greater prevalence of trauma/abuse among women offenders, treatment approaches that target multiple conditions (substance use, mental health, and trauma) simultaneously (i.e., using multimodal models) and account for histories of abuse are most appropriate for women offenders (Holtfreter & Morash, 2003; Wright et al, 2012). Dual diagnoses studies also indicate that women with depression and substance abuse benefit from trauma-informed interventions (Greenfield, Trucco, McHugh, Lincoln, & Gallop, 2007).…”
Section: Multimodal Treatment Effectivenessmentioning
confidence: 99%
“…This selection would avoid wasting resources with people who are not yet ready to desist (and will not benefit from employment) and avoid creating perverse incentives for those who are still actively involved in crime. Until women's risks are properly defined and assessed, the development of programming that best suits their needs will continue to fall short [53,54,84,114,129]. Most importantly, we must infuse all programming with an intersectional orientation that accounts for the many victimization, offending, and reentry contexts that women of different races, classes, sexual orientations, and other social loci must navigate [37,41,89,96].…”
Section: Resultsmentioning
confidence: 99%